Uma investigação sobre a concordância entre as decisões de 1ª e 2ª instâncias proferidas pelo contencioso administrativo tributário do Estado do Ceará - Monteiro, Maria Virgínia Leite (2017)
The present dissertation makes an assessment of the correlation between the results of decisions of 1st and 2nd Instances, made by the Administrative Tax Litigation of the State of Ceará. The objective of the study is to investigate which variables that impact positively and negatively on the agreement between the decisions of the 1st and 2nd instances of CONAT. The research used database obtained from SAPAT Information System, which is the computerized system of CONAT / SEFAZ used to monitoring of the proceedings in CONAT. The econometric model used was the multivariate LOGIT. Evidence were found that the variables “defense” and “appeal at” have a positive impact on concordance of judgments, while the variables “self worth”, “expertise”, and “voluntary action” impacted negatively.